Dynamics of pro-inflammatory and anti-inflammatory cytokine release during acute inflammation in chronic obstructive pulmonary disease: an ex vivo study - Holgate Stephen T; Holloway Rebecca; Hackett Tillie-Louise; Warner Jane A (Respiratory Research, 2008)
Abstract Background Exacerbations of Chronic obstructive pulmonary disease (COPD) are an important cause of the morbidity and mortality associated with the disease. Strategies to reduce exacerbation frequency are thus urgently required and depend on an understanding of the inflammatory milieu associated with exacerbation episodes. Bacterial colonisation has been shown to be related to the degree of airflow obstruction and increased exacerbation frequency. The aim of this study was to asses the kinetics of cytokine release from COPD parenchymal explants using an ex vivo model of lipopolysaccharide (LPS) induced acute inflammation. Methods Lung tissue from 24 patients classified by the GOLD guidelines (7F/17M, age 67.9 ± 2.0 yrs, FEV1 76.3 ± 3.5% of predicted) and 13 subjects with normal lung function (8F,5M, age 55.6 ± 4.1 yrs, FEV1 98.8 ± 4.1% of predicted) was stimulated with 100 ng/ml LPS alone or in combination with either neutralising TNFα or IL-10 antibodies and supernatant collected at 1,2,4,6,24, and 48 hr time points and analysed for IL-1β, IL-5, IL-6, CXCL8, IL-10 and TNFα using ELISA. Following culture, explants were embedded in glycol methacrylate and immunohistochemical staining was conducted to determine the cellular source of TNFα, and numbers of macrophages, neutrophils and mast cells. Results In our study TNFα was the initial and predictive cytokine released followed by IL-6, CXCL8 and IL-10 in the cytokine cascade following LPS exposure. The cytokine cascade was inhibited by the neutralisation of the TNFα released in response to LPS and augmented by the neutralisation of the anti-inflammatory cytokine IL-10. Immunohistochemical analysis indicated that TNFα was predominantly expressed in macrophages and mast cells. When patients were stratified by GOLD status, GOLD I (n = 11) and II (n = 13) individuals had an exaggerated TNFα responses but lacked a robust IL-10 response compared to patients with normal lung function (n = 13). Conclusion We report on a reliable ex vitro model for the investigation of acute lung inflammation and its resolution using lung parenchymal explants from COPD patients. We propose that differences in the production of both TNFα and IL-10 in COPD lung tissue following exposure to bacterial LPS may have important biological implications for both episodes of exacerbation, disease progression and amelioration.